Sepsis index secondary to COVID-19 in patients hospitalized in a reference Paraná's hospital (Research, Society and Development, 2023)
Sepsis secondary to COVID-19 become a serious public health problem during the COVID-19 pandemic. Objective: To evaluate the rate, clinical and epidemiological characteristics of sepsis in hospitalized patients affected by COVID-19 from 2020 to 2021. Method: Field research, descriptive-exploratory, retrospective, documentary, cross-sectional with a quantitative approach, which was developed in a reference in Paraná’s hospital. Datas were collected through a checklist prepared by the researchers in line with the literature on the subject. Results: The medical records of patients hospitalized during the research period were evaluated and, of these, 290 (25.8%) evolved with sepsis and/or septic shock. Of the total number of patients, the majority were elderly males, with chronic diseases and admitted for respiratory complications. The most commonly used procedures were SVD and VM, as well as the use of vasoactive drugs, treatment with antibiotics, prevailing the use of Piperacillin+Tazocin, followed by Ceftriaxone and Meropenem. The most reported was death.